Queloides y cicatrices hipertróficas: problema frecuente de manejo complejo - Lasen D., José Ignacio; Sciaraffia C., Carlos; Parada C., Francisco; Fulla O., Juan; Lombardi A., Juan José (Revista Hospital Clínico Universidad de Chile, 2008)
Keloids and hypertrophic scars are frequent observed. These two conditions are considered part of the abnormal wound-healing spectrum. The main difference between keloids and hypertrophic scars is the scar extension in relation to the original incision, where former extends beyond the original incision while the latter respects it. The main issue with both conditions is that treatment modalities used today offer unacceptable high recurrence rates, between 50 to 70%, when they are applied as monotherapy. With combined treatment modalities recurrence rates have improved partially depending mainly in the chosen combination and so, this strategy is likely the optimal choice for the management of these lesions. The objective of this review was to highlight the pathophysiology, clinical features, and management of keloids with mono or combined therapy, focusing mainly in the surgical and radiotherapy/brachytherapy modalities